Race relations & class conflict as factors in South African history in the 20th Century - Garson, N.G. (My University, 1974)
The use in this paper of the terms race and class has proceeded on the assumption that the historian is absolved from the obligation to contribute anything noteworthy about their meanings as concepts. To do that is the province of the sociologist or the economist. No doubt some social scientists would object to a particular historian's method of testing the usefulness of these concepts as techniques of historical explanation. To the historian that is quite acceptable as fair criticism, provided that he is not saddled with the duty of redefining them as concepts. Another difficulty lies in the fact that many historians, including myself, in terms of our temperament and approach, do not find historical explanation involving the use of large categories of this kind very satisfying. We are more interested in the particular, in specific events and in the actions of specific people. At the same time historians must accept that the social scientists are correct to stress the dimension of the impersonal in attempting to explain social change. When the role of impersonal categories in the past is at issue, the historian has a claim to be heard. For if the historian's grasp of the models and concepts of the social sciences is shaky, perhaps as imperfect is the concrete historical knowledge of many social scientists.
African Studies Seminar series. Paper presented September, 1974